Batch Injection Potentiometry Asam Aspartat, Asam Glutamat dan Arginin Menggunakan Elektroda Tungsten Oksida - Yeni Maulidah Muflihah; Heny Masruroh; Zulfikar Zulfikar (ALCHEMY Jurnal Penelitian Kimia, 2014)
The presence of aspartic acid, glutamic acid and arginine in solution can be detected by potentiometric method using tungsten oxide electrode in a batch system. Characterization of tungsten oxide electrode used include linear range, limit of detection, sensitivity and reproducibility. Buffer type and concentration effect also studied to optimize the measurement results. Optimum conditions for detecting arginine was at pH 6.0 with a phosphate buffer concentration of 0.5 x 10-3 M. Correlation coefficient was obtained for 0.9864, the detection limit of 5.24 x 10-6 M, sensitivity 16.1 mV/decade with reproducibility 0 –7 %. Glutamic acid has a correlation coefficient of 0.9789, the detection limit of 3.80 x 10-6 M, the sensitivity of 9.2 mV/decade and reproducibility of 0 – 6 %. Aspartic acid has a correlation coefficient of 0.9949, the detection limit of 7.76 x 10-6 M, sensitivity of 13.4 mV/decade and reproducibility of 0 – 5 %.